Knowledge, Perceptions and Practices of Malaysian Hajj Pilgrims for Prevention of Influenza-like illness (ILI) in 2013 Hajj Season - ZN, Salmuna; S, Hashim; H, Hasan; A, Abdul Aziz; NN, Nyi; Z, Mohamed; A, Harun; Z, Abdul Rahman (IIUM Medical Journal Malaysia, 2019)
Introduction: Influenza-like illnesses (ILI) were defined as a triad of cough, sore throat and fever. The aim of this study is to determine the changes in knowledge, perceptions and practices towards preventive measures of succumbing to ILI before and after hajj among Malaysian hajj pilgrims. Methodology: An openlabeled randomized control trial study performed on five hundred Malaysian hajj pilgrims in the year 2013. After validated pre-hajj questionnaires completed, 250 subjects were given health education, benzalkonium -based handrub and demonstration of the handrub usage together with pamphlets and labelled as an intervention group. Another 250 subjects from another flight batch were given the same questionnaires without health education with unmedicated hand lotion as a control group. The knowledge, perception, practices and compliances to the handrub practice in both groups were compared with the pre-hajj results. Results: No significant difference between pre and post hajj knowledge and practice among hajj pilgrims in intervention group. Pre hajj perception score [ M (IQR) = 30 (5.00), Z= -2.441, p < 0.05 ] is much higher compared to post hajj perception [ M (IQR) = 29 (6.00), Z = -2.441, p < O.O5 ]. No significant difference between pre and post hajj knowledge, perception and practices among hajj pilgrims in control group. Hand hygiene compliance was not improved with provision of health education and free handrub supply. Conclusion: No significant changes in knowledge, perceptions and practices of Malaysian hajj pilgrims pre and post-hajj in both groups. Provision of handrub did not improved hajj pilgrims compliance.